Does knowing translate to doing? Practitioners' experiences of Circle of Security‐Parenting (COS‐P) training and implementation. Issue 3 (13th April 2020) - Cooper, Deena A.; Coyne, Joe
ABSTRACT: This study sought to understand how practitioners perceive and experience the Circle of Security‐Parenting (COS‐P) training, and further, how they integrate and implement it into practice, and how these experiences influence their use and understanding of the program and its underlying model. A thematic analysis of semistructured interviews at two time points (shortly after training and 3–6 months after training) was used to explore 12 practitioners' experiences of COS‐P training and subsequent implementation. Three main themes were identified; clinical salience, personal salience, and partial use of the program . The findings reflected participants' common perception that the model is relevant and generalizable to a wide variety of contexts. It also highlighted potential barriers to implementation, particularly practitioners' experiences using only components of the COS‐P program in isolation. The results suggest practitioners' assumptions about client complexities, vulnerabilities, and/or incapacities, can prompt practitioners to withhold the use of COS‐P (in part or whole), thereby potentially neglecting key components required for client change. The only participants who implemented the COS‐P training in full had additional training in Circle of Security. RESUMEN: Este estudio buscaba comprender cómo los profesionales de la práctica perciben y experimentan el entrenamiento Círculo de Seguridad‐Crianza (COS‐P), y aún más, cómo ellos lo integran e implementan en la práctica y cómo estas experiencias influyen en su uso y comprensión del programa y el modelo que el mismo enfatiza. Se usó un análisis temático de entrevistas semiestructuradas en dos momentos temporales (poco después del entrenamiento y 3–6 meses después del entrenamiento) para explorar doce experiencias de profesionales de la práctica en cuanto al entrenamiento de COS‐P y la subsecuente implementación. Se identificaron tres temas principales; relevancia clínica, relevancia personal y el uso parcial del programa. Los resultados reflejan la percepción común de los participantes de que el modelo es relevante y se puede generalizar a una variedad amplia de contextos. También destacó barreras potenciales para la implementación, particularmente las experiencias de los profesionales de la práctica usando sólo componentes aislados del COS‐P. Los resultados sugieren que las suposiciones de los profesionales de la práctica acerca de las complejidades, vulnerabilidades y/o incapacidades del cliente pueden dar pie para que tales profesionales no revelen el uso de COS‐P (en parte o totalmente), de modo que potencialmente desatiendan componentes claves requeridos para el cambio en el cliente. Los únicos participantes que implementaron el entrenamiento de COS‐P en su totalidad recibieron entrenamiento adicional en cuanto a Círculo de Seguridad. RÉSUMÉ: Cette étude s'est donné pour but de comprendre comment les praticiens perçoivent et font l'expérience de la formation du Cercle de Sécurité‐Parentage (COS‐P en anglais), et ensuite comment ils l'intègrent et la mettent en place dans leur pratique, ainsi que la manière dont ces expériences influencent leur utilisation et compréhension du programme, tout comme son modèle sous‐jacent. Une analyse thématique d'entretiens semi‐structurés en deux temps (pas longtemps du Cercle de Sécurité‐Parentage (COS‐P) après la formation et 3 à 6 mois après la formation) a été utilisée afin d'explorer à la fois les expériences du COS‐P faites par douze praticiens et leur mise en place subséquente. Trois thèmes principaux ont été identifiés, la saillance clinique, la saillance personnelle et l'utilisation partielle du programme. Les résultats ont reflété la perception commune des participants selon laquelle le modèle est pertinent et généralisable à une grande variété de contextes. L'étude a aussi mis en lumière les barrières potentielles pour la mise en place, en particulier les expériences des praticiens utilisant uniquement des composantes du programme COS‐P en isolation. Les résultats suggèrent que les suppositions des praticiens sur les complexités des clients, leurs vulnérabilités et / ou leurs incapacités, peuvent pousser les praticiens à ne pas utiliser le COS‐P (en partie ou totalement), négligeant ainsi potentiellement des composantes clés exigées pour que le client change. Les seuls participants qui ont mis en place la formation COS‐P en totalité avaient la formation supplémentaire de Cercle de Sécurité. ZUSAMMENFASSUNG: Bedeutet etwas zu wissen, auch es umzusetzen? Erfahrungen von Praktiker_innen mit der Schulung und Implementierung von COS‐P (Circle of Security Parenting) In dieser Studie wurde untersucht, wie Praktiker_innen das COS‐P‐Training (Circle of Security Parenting) wahrnehmen, wie sie es in die Praxis integrieren und wie diese Erfahrungen die Verwendung des Programms sowie das Verständnis des zugrunde liegenden Modells beeinflussen. Eine thematische Analyse von halbstrukturierten Interviews zu zwei Messzeitpunkten (kurz nach dem Training und 3–6 Monate nach dem Training) wurde verwendet, um die Erfahrungen von zwölf Praktiker_innen mit dem COS‐P‐Training und der anschließenden Implementierung zu untersuchen. Es wurden drei Hauptthemen identifiziert; klinische Salienz, persönliche Salienz und partielle Nutzung des Programms. Die Ergebnisse spiegelten die allgemeine Auffassung der Teilnehmenden wider, dass das Modell für eine Vielzahl von Kontexten relevant und verallgemeinerbar ist. Es wurden auch potenzielle Hindernisse für eine erfolgreiche Umsetzung hervorgehoben, insbesondere wenn die Praktiker_innen nur bestimmte Komponenten des COS‐P‐Programms isoliert verwendeten. Die Ergebnisse deuten darauf hin, dass Annahmen der Praktiker_innen bezüglich Komplexität, Vulnerabilität und / oder Unvermögen ihrer Klient_innen dazu führen können, dass das COS‐P (teilweise oder vollständig) nicht angewendet wird. Dadurch werden möglicherweise Schlüsselkomponenten vernachlässigt, die für eine Verhaltensänderung nötig sind. Die einzigen Teilnehmeden, die das COS‐P‐Training vollständig durchgeführt haben, hatten zusätzliche Schulungen in Circle of Security. 抄録: 知識は、実行することに対して十分か？　実践者の「安心感の輪子育て」(COS‐P) トレーニングと実施の経験 本研究では、実践者が「安心感の輪子育て」(COS‐P)トレーニングをどのように 捉え、体験しているのか、そしてさらに、彼らがどのようにそれを実践に統合し て実施していくのか、これらの体験がそのプログラムとその基礎となるモデルの 使用や理解にどのように影響するのか、について理解しようと試みた。COS‐Pト レーニングとその後の実施に関する１２人の実践者の体験を探究するために、２ 回の時点 (トレーニングの直後とトレーニング後３～６ヶ月) での半構造化イン タビューの主題分析が行われた。３つの主なテーマ−臨床的顕著性、個人的顕著 性、プログラムの部分的使用−が特定された。調査結果は、モデルは多種多様な 文脈に関連性があり一般化できるという、実践者の共通の認識を反映していた。 本研究は、実施に対する潜在的な障壁、特に、COS‐Pプログラムの部分のみを使 用する実践者の体験を浮き彫りにした。これらの結果は、クライアントの複雑性、 脆弱性、そして／あるいは、無能力性についての実践者の想定が、COS‐P(の一部、 あるいは全部)の使用を差し控えることと、それによってクライアントの変化に 必要な重要なプログラムの一部が無視されてしまう可能性を、引き起こしている と示唆している。COS‐Pトレーニングの全体を実施したのは、「安心感の輪」に おける追加のトレーニングを受けた実践者のみであった。 摘要: 本研究旨在了解从业者如何感知和体验安全圈养育 (COS‐P) 培训, 并进一步了解他们如何将其整合和实施到实践中, 以及这些经验如何影响他们对该计划及其基本模型的使用和理解。本文采用了两个时间点 (培训后不久和培训后3‐6个月) 的半结构化访谈来进行主题分析, 以探讨12名从业者的COS‐P培训及后续实施的感受。访谈确定了三个主题: 临床显著性, 个人显著性以及对该计划的部分使用情况。调查结果反映了参与者的普遍看法, 即该模型与多种情况相关且具有可推广性, 也强调了实施的潜在障碍, 尤其是从业者仅单独部分使用COS‐P计划的感受。结果表明, 从业者对客户的复杂性、脆弱性, 以及能力不足的假设可能促使从业者停止使用COS‐P (部分或全部), 从而有可能忽略客户改变自身所需的关键部分。唯一全面实施COS‐P培训的参与者在安全圈中进行了额外的培训。 ملخص: هل المعرفة تترجم إلى فعل؟ تجارب الممارسين في الدائرة الآمنة للرعاية الوالدية (COS‐P) من حيث التدريب والتنفيذ سعت هذه الدراسة إلى فهم كيفيه ادراك الممارسين وتجربتهم لتدريب دائره الرعاية الوالدية (COS‐P) ، وكيفيه دمجها وتنفيذها في الممارسة ، وكيف تؤثر هذه التجارب علي استخدامهم وفهمهم للبرنامج والنموذج القائم عليه. تم استخدام تحليل مواضيعي للمقابلات شبه المنظمة في نقطتين زمنيتين (بعد التدريب بفترة وجيزة و بعد 3–6 شهور من التدريب) لاستكشاف تجارب 12 من الممارسين في مجال تدريب الرعاية الوالدية والتنفيذ اللاحق. وتوصل التحليل إلى ثلاثة مواضيع رئيسيه ؛ الاهميه الإكلينيكية ، والبروز الشخصي ، والاستخدام الجزئي للبرنامج. وقد عكست النتائج التصور المشترك للمشاركين بان النموذج مناسب وقابل للتعميم على مجموعة واسعه من السياقات. كما سلطت الضوء علي العوائق المحتملة التي تعترض التنفيذ ، ولا سيما تجارب الممارسين الذين يستخدمون فقط مكونات برنامج (SOC‐P) بشكل منفصل. وتشير النتائج إلى أن افتراضات الممارسين حول تعقيدات العميل ، وجوانب المخاطرة ، والقدرات المتفاوتة ، يمكن ان تدفع الممارسين لوقف استخدام COS‐P (جزئيا أو كليا) ، وبالتالي يحتمل إهمال المكونات الرئيسية المطلوبة لتغيير العميل. وكان المشاركون الوحيدون الذين نفذوا تدريب (COS‐P) بالكامل هم الذين حصلوا على تدريب إضافي في دائرة الأمان.